2018
DOI: 10.1101/458133
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structuring Time in Human Lateral Entorhinal Cortex

Abstract: Remembering event sequences is central to episodic memory and presumably supported by the hippocampal-entorhinal region. We previously demonstrated that the hippocampus maps spatial and temporal distances between events encountered along a route through a virtual city , but the content of entorhinal mnemonic representations remains unclear. Here, we demonstrate that multi-voxel representations in the anterior-lateral entorhinal cortex (alEC) -the human homologue of the rodent lateral entorhinal cortex -specifi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 70 publications
2
7
0
Order By: Relevance
“…Interestingly, our searchlight analysis also revealed a cluster of voxels in lateral entorhinal cortex in association with four-way sequence decoding. This cluster did not survive our a prioricorrected statistical threshold (P < 0.05 small volume correction for bilateral MTL; maximum P = 0.001 uncorrected) but is in line with recent work demonstrating the representation of temporal information in this region in rodents and humans (45)(46)(47). Although our present paradigm is unable to highlight the distinct contributions of the lateral entorhinal cortex compared with the HPC, one possibility is that distinct HPC sequence representations reflecting specific events and temporal durations may be supported by input from entorhinal cortex.…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, our searchlight analysis also revealed a cluster of voxels in lateral entorhinal cortex in association with four-way sequence decoding. This cluster did not survive our a prioricorrected statistical threshold (P < 0.05 small volume correction for bilateral MTL; maximum P = 0.001 uncorrected) but is in line with recent work demonstrating the representation of temporal information in this region in rodents and humans (45)(46)(47). Although our present paradigm is unable to highlight the distinct contributions of the lateral entorhinal cortex compared with the HPC, one possibility is that distinct HPC sequence representations reflecting specific events and temporal durations may be supported by input from entorhinal cortex.…”
Section: Discussionsupporting
confidence: 86%
“…It arises spontaneously and covers the temporal granularities expected of a code supporting encoding of episodic memories. These findings are paralleled by reports from human fMRI studies reporting that activity patterns in entorhinal cortex, including its lateral part, continuously change during encoding of an experience and that the amounts of change during encoding is related to later recalled duration of the same experience (Bellmund et al, ; Lositsky et al, ). Even though it is currently not known how the temporal signals in the entorhinal–hippocampal circuits are related, it is tempting to suggest that both the formation of time cell sequences and the drifting activity in hippocampus could be driven by the temporal signals in LEC which covers both of these scales.…”
Section: Population Activity In Entorhinal Cortex and Hippocampus Varsupporting
confidence: 54%
“…The drifting representations of CA2 and CA1 arise spontaneously as required; however, the temporal drift occurs on the scales of hours that is not necessarily sufficient to capture the details of a typical episode. Recent electrophysiological studies in rodents and fMRI studies in humans suggest that a likely source of temporal information is found in the lateral entorhinal cortex (LEC) (Bellmund, Deuker, & Doeller, ; Montchal, Reagh, & Yassa, ; Tsao et al, ). We recorded LEC neurons while rats were freely foraging in an arena for 12 trials each lasting about 4 min (Figure c).…”
Section: Population Activity In Entorhinal Cortex and Hippocampus Varmentioning
confidence: 99%
“…To match the coordinates resulting from MDS to the original positions in the virtual environment we used Procrustes analysis allowing translation, scaling, reflection and rotation (see Bellmund et al 74 for an application of the combination of multidimensional scaling and Procrustes analysis to fMRI data). The goodness of fit, the Procrustes distance, was quantified by the normalized sum of squared errors between reconstructed and true coordinates and was compared to Procrustes distances resulting from Procrustes analyses of the MDS coordinates and sets of coordinates in which the assignment of object identity to position was shuffled, yielding a surrogate distribution from all 720 possible permutations.…”
Section: Reconstructing Remembered Positionsmentioning
confidence: 99%